Suicidal behavior and self-harm in girls with eating disorders - Koutek J (Dove Medical Press, 2016)
Jiri Koutek, Jana Kocourkova, Iva Dudova Department of Child Psychiatry, Charles University Second Faculty of Medicine, University Hospital Motol, Prague, Czech Republic Abstract: Comorbid psychopathology, including self-harm and suicidal behavior, is often found in patients with eating disorders. To better understand the reasons for high comorbid psychopathology among eating disorders, self-harm, and suicidal behavior, we examined this comorbidity in female patients hospitalized with eating disorders. In a sample of 47 girls admitted for anorexia nervosa, atypical anorexia nervosa, and bulimia nervosa, 72% had depressive symptoms, 11% had obsessive-compulsive symptoms, 9% had anxiety disorder, 23% had substance abuse, and 57% had disharmonious personality development. Suicidal behavior was present in 60% of patients and self-harm in 49%. Association was found between self-harm and suicidality. In all, 68% of girls with eating disorders had a positive score in the Children’s Depression Inventory questionnaire and 62% of them in the Child Adolescent Suicidal Potential Index questionnaire. Clinical examination of girls with eating disorders should focus on identifying the risk of suicidal behavior and self-harm. Keywords: eating disorders, child, adolescent, self-harm, suicidal behavior